If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-96=-8(5+v)
We move all terms to the left:
-96-(-8(5+v))=0
We add all the numbers together, and all the variables
-(-8(v+5))-96=0
We calculate terms in parentheses: -(-8(v+5)), so:We get rid of parentheses
-8(v+5)
We multiply parentheses
-8v-40
Back to the equation:
-(-8v-40)
8v+40-96=0
We add all the numbers together, and all the variables
8v-56=0
We move all terms containing v to the left, all other terms to the right
8v=56
v=56/8
v=7
| 4(2-x)=2(x+1) | | -30x+32x=−15 | | 32/38=w/7 | | 5(10)^x=54 | | 2(x+6)-6=5x+1 | | -12-5n=-8-4n | | 3x-5/3=55 | | -7x-7=6x+19 | | 7n-2+6n=24 | | 23=-2(-6b-6)-(1+8b) | | 3x^2+5x=2x | | 60-5x-4.9x^2=0 | | 1/6h+1/2=3/4h^2 | | -3(-2v+3)-8(3v-6)=3 | | v+7/8=1/2 | | j^2+11j=-28 | | -12=2(5+5a)+6(a+7) | | 3(3x+4)=x-4 | | 5b-3(7+5b)=-101 | | x/3~+5=x-1 | | -3-4m=-8-4m | | 2x-5=1/5x+7 | | 7y-6=20 | | 19p=-16 | | -28-4m=-2m-8(m-1) | | 11-16x=10x-3 | | –3.5(2–3n)–2.5=n | | -8y+3(y-3)=21 | | 5x^2+3=3x | | 7n-5=9n+12 | | 5+7(6-6x)=299 | | 8-8a=-3a-2 |